2006
DOI: 10.1300/j006v26n03_05
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Issues in Children with Physical Disabilities and Their Families

Abstract: Sleep has a significant impact on the daily functioning of children and their parents. The purpose of this study was to describe the sleep patterns, issues, and strategies used to facilitate sleep in children with and without physical disabilities and their families. Data were collected from questionnaires completed by caregivers and siblings. Caregivers of children with physical disabilities reported significantly greater concerns regarding general sleep problems, safety, and discomfort at night, night wakeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(66 citation statements)
references
References 0 publications
6
56
4
Order By: Relevance
“…Some studies focused on how typical routines and rituals (e.g., during mealtimes, bedtimes) were used as strategies, while others focused on how new routines and rituals were developed to meet the condition's challenges. In two studies with pediatric samples, one in the context of physical disabilities (Wright et al, 2006) and the other of ASD (Larson, 2006), parents reported that implementing a bedtime routine was a strategy to improve children's sleep by providing a sense of comfort and predictability. Mothers of children with ASD considered bedtime routine helpful in managing their children's anxiety (Larson, 2006; Marquenie et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies focused on how typical routines and rituals (e.g., during mealtimes, bedtimes) were used as strategies, while others focused on how new routines and rituals were developed to meet the condition's challenges. In two studies with pediatric samples, one in the context of physical disabilities (Wright et al, 2006) and the other of ASD (Larson, 2006), parents reported that implementing a bedtime routine was a strategy to improve children's sleep by providing a sense of comfort and predictability. Mothers of children with ASD considered bedtime routine helpful in managing their children's anxiety (Larson, 2006; Marquenie et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported pain to be the strongest contributing factor to sleep problems in a population of children with physical disabilities. 43,44 Moreover, a recent study done on 35 children with bilateral cerebral palsy (ie, spastic quadriplegia or diplegia) and severe spasticity showed an improvement in the frequency of nighttime awakening along with objective severity of pain within 6 months following the implantation of an intrathecal baclofen pump. 45 One study done on a population of adults with spasticity of varying origins showed similar results with improvement in sleep quality and quantity after the aggressive treatment of underlying spasticity with intrathecal baclofen.…”
Section: Abnormal Tone and Painmentioning
confidence: 99%
“…5,6,8,12,43 In the same population, previous studies have shown that parents of children with sleep problems feel more stressed and irritable and relate that their child's sleep problems affect their own daytime lives and represent an extra demand on already limited personal time and energy. 5,11,12,44 In one study, parents also believed that as a result they had a relatively impoverished social life. 5 Conversely, family stressors may negatively affect a child's sleep pattern.…”
Section: Consequences Of Sleep Problems On the Child And The Familymentioning
confidence: 99%
“…Sleep problems increase when pain is reported in populations of youth with physical disabilities (e.g. Wright et al, 2006) and intellectual disabilities (ID) (Ghanizadeh and Faghih, 2009). One previous study has examined the potential relationships between sleep problems and pain in youth with IDD, including ASD (Breau and Camfield, 2011).…”
Section: Relationships Between Sleep Problems Pain and Asdmentioning
confidence: 99%